Ludzie uniwersytetu - Drozdowicz, Zbigniew (Polska Akademia Nauk - "Nauka", 2013)
My attempts are being focused to present the complexity of situations, in which university people were put into to fulfill their mission. It happened and happens still today that in such realizations they are being approached by allies and such forces which are willing and are able to understand the social role of universities. However, often they had met and still meet such opponents who are able to successfully make their professional and private life a pain. If they despite these obstacles are able to realize their tasks and calls it is due to their specific personality. I would like to omit the pathos here. Briefly said, these are the personalities who believe in the sense of pursuing knowledge, to transmit it to others and being ready to sacrifice much in these attempts, even the feeling of personal security who we all need to a normal life.
Keywords: university traditions; global conditions of university life; modern threats and challenges; local conditions of university life